Impact of Percutaneous Renal Access Technique on Outcomes of Percutaneous Nephrolithotomy - TEPELER, Abdulkadir; ARMAGAN, Abdullah; AKMAN, Tolga; POLAT, Emre Can; Ersoz, CEVPER; ERSÖZ, CEVPER; TOPAKTAS, Ramazan; ERDEM, Mehmet Remzi; ONOL, Sinasi Yavuz (My University, 2012)
Background and Purpose: Percutaneous nephrolithotomy (PCNL) is regarded as the gold standard for the treatment of patients with renal stones larger than 2 cm in diameter. Creating a percutaneous renal access is the initial and probably the most important step in performing a PCNL. Two primary methods of obtaining proper percutaneous renal access under fluoroscopic guidance are described: The -triangulation- and the -eye of the needle- techniques. In this article, we compare these two techniques in terms of success and complication rates.